ASSESSMENT METHOD ECONOMICALLY VALUE ADDED AS BASIS OF MEASUREMENT OF THE INTELLECTUAL CAPITAL OF THE ENTERPRISE - N. Danilochkina; M. Sazonova; N. Cherner (Вестник университета)
The measurement method economically of the value added received by the enterprise from growth of profitability of the industry average level has considered. Three main approaches are a part of this method: «custonomics» directed to assessment of the capital which is brought on the enterprise by constant consumers, «workonomics» directed to assessment of the human capital and «supplynomics», directed to value added assessment on the supplier. The method allows to estimate the value added of the organization created by the main components of its intellectual capital.